Digitalization and Inclusive Education: Digital Accessibility for Students with Special Needs in the Era of Educational Transformation - Ahmad Asroni (Educazione: Journal of Education and Learning, 2025)
This study examines the role of digitalization in strengthening inclusive education through the development of digital accessibility for students with special needs in the era of educational transformation. The rapid advancement of information and communication technology has significantly transformed educational systems by expanding access to learning resources, promoting flexible learning environments, and supporting personalized learning experiences. However, despite its potential benefits, educational digitalization continues to face substantial challenges related to inequality, digital accessibility, and the exclusion of marginalized groups, particularly students with disabilities. This article employs a qualitative approach using library research methods by analyzing various academic sources, policy documents, and international reports related to inclusive education, digital accessibility, and educational technology. The findings indicate that digital technologies, including assistive technologies, artificial intelligence, online learning platforms, and Universal Design for Learning (UDL), play a crucial role in reducing learning barriers and enhancing educational participation among students with special needs. Nevertheless, the implementation of inclusive digital education remains constrained by inadequate infrastructure, limited digital literacy, insufficient teacher competencies, high costs of assistive technologies, and persistent social stigma toward people with disabilities. The study emphasizes that educational digitalization should not merely focus on technological modernization, but also on promoting social justice, equality, and human rights in education. Therefore, collaborative efforts among governments, educational institutions, technology developers, and communities are essential to establish inclusive, accessible, and equitable educational systems in the digital era